Synthesis and characterization of αM-conotoxin SIIID, a reversible human α7 nicotinic acetylcholine receptor antagonist. (30th April 2022) - Wang, Hongxing; Li, Yubin; Yang, Manyi; Zhou, Maojun
Abstract: α-Conotoxins, a group of small marine peptide toxins that target nAChRs with high potency and selectivity, are valuable pharmacological tools and potential drug leads. In this study, we reported the synthesis and physiological functions of a novel αM-superfamily conotoxin SIIID (CCGEGSSCPKYFKNNFICGCC) from a fish-hunting Conus striatus . Three SIIID isomers with different cystine connectivities were synthesized by solid-phase polypeptide synthesis and confirmed by mass spectrometry. Patch clamp experiments on HEK293 cells expressing nAChR subtypes showed that 1 μM SIIID (1–4, 2–5, 3–6) inhibited PNU-120596 and acetylcholine induced human α7 nAChR currents by 48.45%, which was higher than 5.08% of SIIID (1–5, 2–4, 3–6) and 9.57% of SIIID (1–6, 2–4, 3–5). Further study on the most active SIIID isomer showed that 10 μM SIIID inhibited PNU-120596 and acetylcholine induced human α7 nAChR currents by 76.33% but had no obvious effect on acetylcholine induced human α3β4 nAChR currents. In addition, SIIID inhibited PNU-120596 and acetylcholine induced human α7 nAChR currents with an IC50 value of 880.71 ± 271.91 nM, and this inhibition was reversible. Patch clamp experiments on rat DRG neurons showed that 10 μM SIIID had <15% inhibitory effects on sodium, potassium and calcium currents. Our results suggested that SIIID would be a promising neuropharmacology tool for the study of human α7 nAChR and its related diseases. Graphical abstract: Image 1 Highlights: SIIID (1–4, 2–5, 3–6) was the most active of the three isomers. 10 μM SIIID had <15% inhibitory effects on the sodium, potassium and calcium currents. 10 μM SIIID had no obvious effect on the human α3β4 nicotinic acetylcholine receptor currents. 10 μM SIIID inhibited the human α7 nicotinic acetylcholine receptor currents by 76.33%. SIIID inhibited human α7 nAChR currents with a 50% inhibiting concentration value of 880.71 ± 271.91 nM.